1997
DOI: 10.1007/s004150050066
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled trial of mitoxantrone in relapsing-remitting multiple sclerosis: 24-month clinical and MRI outcome

Abstract: We designed a randomized, placebo-controlled, multicentre trial involving 51 relapsing-remitting multiple sclerosis patients to determine the clinical efficacy of mitoxantrone treatment over 2 years. Patients were allocated either to the mitoxantrone group (27 patients receiving I.V. infusion of mitoxantrone every month for 1 year at the dosage of 8 mg/m2) or to the placebo group (24 patients, receiving I.V. infusion of saline every month for 1 year) using a centralized randomization system. Disability at entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
2
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(164 citation statements)
references
References 26 publications
(26 reference statements)
8
144
2
10
Order By: Relevance
“…In fact, benefit can be seen in disease progression in patients with secondary progressive MS (SPMS) 1 3 -1 5 . Randomized studies has also showed reduction of relapsing and new lesions incidence using magnetic resonance imaging (MRI) [16][17][18] . Mitoxantrone (MX) acts as an immunosupressive agent which alters B and T lymphocytes responses to central nervous system (CNS) antigens, and through this process it seems to avoid axonal lesion and macrophages mediated demyelination [1][2][3][4][5][6][7][8][9]13,19 .…”
Section: Mitoxantrone Hydrochloride (Novantronementioning
confidence: 99%
“…In fact, benefit can be seen in disease progression in patients with secondary progressive MS (SPMS) 1 3 -1 5 . Randomized studies has also showed reduction of relapsing and new lesions incidence using magnetic resonance imaging (MRI) [16][17][18] . Mitoxantrone (MX) acts as an immunosupressive agent which alters B and T lymphocytes responses to central nervous system (CNS) antigens, and through this process it seems to avoid axonal lesion and macrophages mediated demyelination [1][2][3][4][5][6][7][8][9]13,19 .…”
Section: Mitoxantrone Hydrochloride (Novantronementioning
confidence: 99%
“…La mitoxantrone est utilisée dans la SEP comme agent immunosuppresseur. Plusieurs études ont montré qu'elle réduisait le nombre de poussées, l'apparition de nouvelles lésions rehaussées par le gadolinium (ce qui traduit une rupture de la barrière hémato-encéphalique) 1 et la progression du handicap [2][3][4]. L'efficacité de la mitoxantrone se maintient plusieurs mois après l'arrêt du traitement.…”
Section: Les Traitements De Deuxième Ligne : Pour Les Formes Actives unclassified
“…2) In an Italian trial, the efficacy of mitoxantrone was assessed in 51 patients with relapsing-remitting MS. 13 The patients were randomized and received either mitoxantrone (8 mg/m 2 body surface) or a placebo. Clinical assessment was performed by blinded physicians.…”
Section: Studies In Msmentioning
confidence: 99%